EVOLUTION OF THE BüKK MOUNTAINS (NE HUNGARY) DURING THE MIDDLE–LATE TRIASSIC ASYMMETRIC RIFTING OF THE VARDAR-MELIATA BRANCH OF THE NEOTETHYS OCEAN - Velledits F. (My University, 2006)
Based on sedimentological and biostratigraphic investigations of the Middle–Late Triassic successions of the Bükk Mountains, the evolution of an upper plate margin of a rifting area was reconstructed. The Middle Anisian shallow water carbonates are succeeded by terrestrial sediments. Simultaneously with the uplift, volcanic activity starts, indicating the beginning of the rifting. The emersion was followed by rapid subsidence in the Late Anisian–Early Ladinian which corresponds to the synrift stage. Based on facies distribution of Ladinian–Carnian sediments, the half-graben structure of the basement can be outlined. Coeval existence of platforms and basins is characteristic of this period. From the end of the Fassanian, the subsidence slows down: postrift stage. At this time the thermal cooling controls the subsidence of the area. During the Late Triassic, the edges of the platforms were gradually drowned and basins conquered bigger and bigger areas. Sediments deposited on the southern shelf of the opening Vardar-Meliata branch of the Neotethys Ocean show features characteristic to the upper plate part of a rifting area, whereas sediments of the northern shelf show features characteristic to the lower plate. The opening of the Vardar-Meliata branch of the Neotethys Ocean follows the asymmetric rifting model of Wernicke (Can J Earth Sci 22:108–125, 1985) and Dixon et al. (Tectonics 8(6):1193–1216, 1989).
Keywords: MIDDLE-LATE TRIASSIC; RIFTING; NEOTETHYS; ANISIAN TERRESTRIAL SEDIMENTS; PLATFORM/BASIN EVOLUTION; Carnian; Ladinian; Anisian; Mesozoic::Triassic::Upper::Carnian; Мезозой::Триасовая::Верхний::Карнийский; Mesozoic::Triassic::Middle::Ladinian; Мезозой::Триасовая::Средний::Ладинский; Mesozoic::Triassic::Middle::Anisian; Мезозой::Триасовая::Средний::Анизийский